Treatment of the critically ischaemic lower limb. - Shields, D. A. (BMJ Group, 1994)
Medical therapy of PAOD is only indicated in patients unsuitable for vascular reconstruction or angioplasty. The approach includes early detection of subjects at risk, avoidance of known risk factors, and appropriate management of diseases such as diabetes and hypertension. Vasodilators are of little use orally, though some drugs may have a part to play for short-term management and iloprost should be considered for patients unsuitable for revascularization. The ankle systolic or toe pressure should be used as a measure of disease and, if reduced, arteriography should be performed. This should not be limited to those thought fit for major surgery, as angioplasty or thrombolytic therapy may be appropriate, and aortoiliac disease may be treated by extra-anatomic bypass if not suitable for major surgery. Arterial reconstruction is associated with a reduction in both mortality and amputation, and should be attempted if a greater than 25% chance of limb salvage could be expected.